(untitled) (Bangladesh Rice Journal, 2020)
Incidence of insect pests and their associated natural enemies was investigated from July 2017- June 2018 at six locations (Gazipur, Rajshahi, Barishal, Sonagazi, Rangpur, Cumilla) of Bangladesh to identify their major occurrence period as well as their incidence in three rice growing seasons, (Aus, T. Aman, and Boro). Among the tested locations, marked differences were found in the composition of insect pest and natural enemies. Higher number of pest population was found at Gazipur with 80,000 individuals for insect pest and 40,000 individuals for natural enemies. At least one peak for major insect pest and natural enemies suggested their specific occurrence period across the locations. Among the insect pests, major peak of GLH was found at Gazipur and Rajshahi during T. Aman season with 4,000 individuals for each location. In contrast, BPH population was as high as 10,000 individuals for Gazipur in October during T. Aman season. Additionally, it was high at Rajshahi in October and November with around 2,000 individuals of BPH. For WBPH, one major peak was found in October at Gazipur and Rajshahi with 10,000 and 2,000 individuals respectively. For YSB, it was higher at Rajshahi in October with over 6,000 individuals during T. Aman season. Moreover, one major peak also observed in Barishal with over 2,000 individuals in November. Among natural enemies, CDB population was observed mainly at three locations in between October and November with 900 individuals for Gazipur, 400 individuals for Rajshahi and 200 individuals for Barishal during T. Aman season. In contrast, for STPD population, two major peaks were found in Barishal with 6,000 and 5,000 individuals in December and March respectively during Boro season. For GMB population, it was observed at Gazipur in November with more than 20,000 individuals during T. Aman season whereas Rajshahi had around 2,000 individuals in the same month. However, higher incidence of GLH, BPH, and WBPH at Gazipur and Rajshahi suggested availability of insect pests during T. Aman season. In contrast, higher YSB incidence at Barishal and Rajshahi indicated their abundance in those areas. On the other hand, incidence of natural enemies at Gazipur indicated presence of greater biological control compared with other locations. In future, this information could serve as a reliable source in strengthening rice pest monitoring services as well as effective pest control in Bangladesh. Bangladesh Rice j. 2019, 23(1): 35-43